Prosedur Pemeriksaan CT Scan Kepala Dengan Klinis Stroke Hemorrhagic Di RS Bhayangkara Makassar - Irma Rizky; Ni Putu Rita Jeniyanthi; Cokorda Istri Ary Widiastuti (Journal of Educational Innovation and Public Health, 2024)
Background: CT Scan is a medical technology that can show images in the form of slices to see the anatomy of the human body because this technology combines X-rays and television. Basically, how a CT scan works uses a radiation source from X-rays. There are various examinations that can be carried out using a CT scan, one of which is a head examination with a CT scan. CT scan of the head at the Radiology Installation at Bhayangkara Hospital Makassar uses a Slice Thickness of 3 mm to produce a better image. The aim of this research is to determine the Head CT Scan Examination Procedure for Clinical Hemorrhagic Stroke in the Radiology Installation of Bhayangkara Hospital, Makassar. Results: The results of this study indicate that the CT scan procedure of the head with clinical hemorrhagic stroke at the radiology installation at Bhayangkara Hospital, Makassar was carried out without any special preparation but the patient was instructed to remove metal objects or accessories around the head such as earrings, hairpins and necklaces. Using a slice thickness of 3 mm is good enough to display image results and confirm the diagnosis. Conclusion: The head CT scan procedure for clinical hemorrhagic stroke was carried out using the head first protocol. The slice thickness used in this examination is 3 mm. The choice of slice thickness is the biggest factor because a thick slice thickness will produce images with low detail and cause artifacts, whereas a thin size will produce images with high detail but there is noise in the image.